AUDIT REPORT LAG PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - WIDYAWATI LEKOK; VERLIN RUSLY (Media Bisnis, 2020)
This research examines the factors that influence audit report lag. The independent variables in this research are firm size, profitability, solvability, accounting firm size, age of company, audit committee size, independent board of commissioners, and ownership concentration. Audit report lag as the dependent variable in this research. The research population is manufacturing companies listed on the Indonesia Stock Exchange for the period of 2016-2018. There are 228 data that meet the sample criteria. The samples are collected using purposive sampling method. This research is analyzed using multiple regression analysis. The result identified that firm size, profitability, age of company had influence on audit report lag. While solvability, accounting firm size, audit committee size, independent board of commissioners, and ownership concentration had no influence on audit report lag.